Informetric analysis and review of literature on the role of BIM in sustainable construction - Santos, Rúben; Costa, António Aguiar; Silvestre, José D.; Pyl, Lincy (Automation in construction, 2019)
The construction industry and researchers have been exploring new techniques to improve the sustainability of buildings. One such solution is the use of a recent technology such as building information modelling (BIM). Accordingly, the present article reviews the current state of literature on sustainable construction and BIM, including the latter's evolution. In contrast to previous reviews on this subject, the present work has a broader scope that covers the environmental, economic, and social dimensions and their combinations. To obtain a comprehensive review, the authors conducted an informetric analysis of the literature and categorised it based on a content analysis. A total of 11 different terms and 28 combinations were used to collect relevant literature on this subject, resulting in a total of 317 journal articles for the period between 2008 and 2017. The information obtained from informetric analysis was later validated by a content analysis, in which gaps and trends were identified. It was observed that publications on this subject registered an exponential growth, with 90% of the articles being published in the last five years. The authors identified a gap in literature pertaining to the integration of the three dimensions of sustainability; however, literature on the integration of sustainable performance and BIM has grown considerably in recent years, which indicates that BIM is increasingly being used as a reliable method for sustainable construction practices. •Between 2008 and 2017, 317 journal articles were published on this subject.•Higher dispersion of the literature show that BIM has higher synergies presently.•LCA, LCC, and CFD are the most used methods, while IFC potential is often explored.•There is a gap in the literature that integrates all dimensions of sustainability.•Future research on BIM-GIS, BIM libraries, and Big Data methods is expected.